P-doped multiwall carbon nanotube/perylene diimide derivative photoelectrochemical cells for photocurrent generation - Troeger, Anna; Ledendecker, Marc; Margraf, Johannes; Sgobba, Vito; Guldi, Dirk Michael; Vieweg, Benito; Spiecker, Erdmann; Suraru, Sabin-Lucian; Wuerthner, Frank (Advanced Energy Materials, 2012)
A perylene diimide (PDI) derivative bearing four chlorine substituents in the bay area is deposited together with pristine multiwall carbon nanotubes (MWNTs) and/or Nafion p-doped MWNTs (p-MWNTs) onto indium tin oxide (ITO) solid substrates by means of air-brushing. The resulting photoanodes are studied in photoelectrochemical cells and reveal highest photocurrent efficiencies when PDI and p-MWNT are combined as photoactive materials, indicating the beneficial effect of Nafion.